2006
DOI: 10.1007/s10237-006-0038-x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Growth of Cartilage Rudiments may Generate Perichondrial Structures by Mechanical Induction

Abstract: Experimental and theoretical research suggest that mechanical stimuli may play a role in morphogenesis. We investigated whether theoretically predicted patterns of stress and strain generated during the growth of a skeletal condensation are similar to in vivo expression patterns of chondrogenic and osteogenic genes. The analysis showed that predicted patterns of compressive hydrostatic stress (pressure) correspond to the expression patterns of chondrogenic genes, and predicted patterns of tensile strain corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…The points depicted in the figure represent both primary cells and cells lines, which have been demonstrated to have similar properties. 1 Pa = 10 dyn/cm 2 (after Anderson and Knothe Tate 2007a) [McBeath et al 2004, Meinel et al 2004, Knippenberg et al 2005, David et al 2007, Akimoto et al 2005, Baksh et al 2006, Campbell et al 2006, Takahashi et al 1998, Miyhanishi et al 2006, Hillsley and Frangos 1994, Billotte et al 2001, Klein-Nulend et al 1986, Wong and Carter 1990, Henderson et al 2007, Angele et al 2003, Roelofsen et al 1995, Illi et al 2005]. …”
Section: Discussion and Future Outlookmentioning
confidence: 99%
“…The points depicted in the figure represent both primary cells and cells lines, which have been demonstrated to have similar properties. 1 Pa = 10 dyn/cm 2 (after Anderson and Knothe Tate 2007a) [McBeath et al 2004, Meinel et al 2004, Knippenberg et al 2005, David et al 2007, Akimoto et al 2005, Baksh et al 2006, Campbell et al 2006, Takahashi et al 1998, Miyhanishi et al 2006, Hillsley and Frangos 1994, Billotte et al 2001, Klein-Nulend et al 1986, Wong and Carter 1990, Henderson et al 2007, Angele et al 2003, Roelofsen et al 1995, Illi et al 2005]. …”
Section: Discussion and Future Outlookmentioning
confidence: 99%
“…These in vitro environments can better mimic dynamic processes that exist in vivo, such as morphogenetic deformations [11][12][13][14][15][16][17] and extracellular matrix (ECM) remodelling [18][19][20]. For example, materials with mechanically or magnetically actuated surface topography or altered stiffness can change cell morphology [21][22][23] and lineage specification [24].…”
Section: Introductionmentioning
confidence: 99%
“…The flattened appearance of cells in the perichondrium, which is the precursor to periosteum, suggests that cells are under tension in the longitudinal and circumferential directions (Figure 1; Rooney and Archer 1992;Henderson et al 2007). During development, bone growth in circumference occurs through the process of periosteal bone apposition and in length through endochondral ossification.…”
Section: Introductionmentioning
confidence: 95%
“…During development, bone growth in circumference occurs through the process of periosteal bone apposition and in length through endochondral ossification. Previous studies have suggested that circumferential tension in the perichondrium/periosteum may influence the ossification of the bone collar, which occurs through periosteal bone apposition (Henderson et al 2007). Additionally, it has been suggested that the longitudinal tensile stresses in the periosteum apply compressive loads across the growth plate, thereby restraining endochondral ossification at the physis (D'Souza and Shah 1999).…”
Section: Introductionmentioning
confidence: 98%